Parents with Serious Mental Illness Served by Peer Support Specialists - M. Weston, Shannon (International Journal of Psychosocial Rehabilitation, 2017)
Parents with a mental illness, especially single mothers, who are caring for their children are particularly vulnerable to social isolation, stress, financial hardship, and lack of resources. Prevention and strengths-based interventions are needed for mothers with serious mental illness and their children. Current mental health interventions tend to focus on the individual without respect to family context and do not address parenting needs or support for both the parent and child. The literature indicates mothers with a mental illness and their children should be considered a high-risk group in need of more intensive and more frequent mental health supports. One alternative for more frequent mental health support is through the peer support specialist model. Although the peer support specialist model is a nationally recognized evidence- based practice, research is limited on identifying the program and service needs of parents with mental illness from a peer support specialist perspective. This study implemented an exploratory investigation to identify life stressors and specialized programs and service needs for parents with mental illness from a peer support specialist perspective. Results of this study identified support groups for parents with mental illness and for youth/young adults with a parent with a mental illness as the highest level of need. Results also found a need for peer support specialists to be paired with individuals based on mutual characteristics of parental status and identification of having a parent with a mental illness